Decoding the Ideal Mathematics Classroom: A Qualitative Study on Secondary School Students’ Perceptions in Iran - Shekarabi, Farkhondeh Hosseini (EDUPEDIA Publisher, 2025)
Purpose – This study explores secondary school students’ perspectives on the factors that create an ideal mathematics classroom. While prior research has emphasized curriculum and content delivery, fewer studies have systematically examined students’ own voices regarding classroom dynamics, teacher influence, and learning environments. Methodology – A qualitative design was employed, involving free-form reflective essays written by 390 students from three public secondary schools. Students were prompted to describe their classroom experiences and identify elements they found most impactful for their learning. The essays were analyzed thematically to uncover key categories and emerging themes. Findings – The analysis revealed that relatively few students emphasized content knowledge as a central element. Instead, the majority highlighted engaging instructional methods, teacher personality and behavior, and positive teacher–student relationships as most critical to their learning. A joyful, interactive classroom environment was consistently described as essential for motivation and understanding. Students also indicated that class length and scheduling significantly shaped their learning experiences. These findings suggest the need to balance pedagogy and content delivery while ensuring classroom environments remain supportive and engaging. Novelty – By foregrounding students’ narratives, this study contributes original insights into learner-centered perspectives in mathematics education. It highlights the importance of affective and relational factors, often underrepresented in policy-oriented curriculum reforms. Significance – The findings provide valuable guidance for mathematics teachers, curriculum developers, and policymakers. Incorporating students’ perspectives into curriculum design and teaching practices can foster more inclusive, responsive, and effective mathematics classrooms.